Removal of soluble microbial products and dyes using heavy metal wastes decorated on eggshell. (May 2021) - Lin, Ting-Yang; Chai, Wai Siong; Chen, Shu-Jen; Shih, Jeng-Ywan; Koyande, Apurav Krishna; Liu, Bing-Lan; Chang, Yu-Kaung
Abstract: This work studied the potential of using eggshell (ES) (200–300 μm) waste as adsorbent for sequential removal of heavy metals, soluble microbial products, and dye wastes. In this study, among soluble microbial products, chicken egg white (CEW) proteins were selected as simulated contaminants. ES was applied to capture heavy metal ions (e.g., Cu 2+ and Zn 2+ ) and the formed eggshell metal (ES-M) complex was use to absorb soluble microbial products (e.g., soluble proteins), followed by subsequent removal of dyes from aqueous solutions using ES-M-CEW adsorbent. The experimental conditions for the adsorption of CEW proteins by ES-M include shaking rate, adsorption pH, isothermal and kinetic studies. The maximum protein adsorption by ES-Zn and ES-Cu were 175.67 and 153.65 mg/g, respectively. Optimal removal efficiencies of the ES-M-CEW particles for Acid Orange (AO7) and Toluidine blue (TBO) dyes were at pH 2 and 12, respectively, achieving performance of 75.38 and 114.18 mg/g, respectively. The removal of TBO dye by ES-M-CEW adsorbent was equilibrated at 5 min. The results showed that low cost and simple preparation of the modified ES particles are feasible for treating various wastewaters. Graphical abstract: Image 1 Highlights: Modified eggshell (ES) particles shown to be feasible to treat various wastewaters. Removal of heavy metal ions, CEW proteins and dyes studied using ES waste. Maximum protein adsorption was 175.67 and 153.65 mg/g for ES-Zn and ES-Cu. Optimal dye removal efficiency with ES-M-CEW was 75.38 mg/g (A07) and 114.18 mg/g (TBO).